Niveles de abertura como estrategia de enseñanza en la simulación de espectros de absorción de rayos-X (XAS). Aplicados a modelos biomoleculares. (2020)
Computational approaches to simulate spectra of multiple analytical techniques and evaluations of experimental data have gained importance in recent years in teaching at the undergraduate level. This manuscript presents a teaching strategy that trains students in the basic skills of obtaining simulated spectra within the framework of the ATOMS, ARTEMIS, ATHENA software. In addition, students can simulate X-ray absorption spectra (XAS) from various prosthetic groups with high biological relevance, a cornerstone of the enzyme, and a key topic in many undergraduate biochemistry courses. Additionally, students can simulate X-ray absorption spectra (XAS) from various prosthetic groups with high biological relevance, a cornerstone of the enzyme, and a key topic in many undergraduate biochemistry courses. Several examples of spectrum simulation are introduced here from available crystallographic information for various types of hemoglobin, vitamin b12, rubredoxin and carbonic anhydrase. In addition, an example of molecular refinement and an XAS application were applied to understand bacterial metabolic processes. This practice develops understanding in the areas of bioinorganic chemistry, spectroscopy, coding skills, and XAS spectrum analysis. An application-based guide for undergraduate students was obtained.